Removal of Ciprofloxacin Antibiotic from Synthesized Aqueous Solution Using Three Different Metals Nanoparticles Synthesized Through the Green Method - Shakorfow, Abdelmalik Milad; Al Mhanna, Najah; Atiya, Mohammed A.; Hassan, Ahmed K.; Kadhim, Fatimah Q.; Mahmoud, Zainab A.; Abbas, Azza Hashim (Al-Khwarizmi Engineering Journal, 2023)
This study investigates the possibility of removing ciprofloxacin (CIP) using three types of adsorbent based on green-prepared iron nanoparticles (Fe.NPs), copper nanoparticles (Cu. NPS), and silver nanoparticles (Ag. NPS) from synthesized aqueous solution. They were characterized using different analysis methods. According to the characterization findings, each prepared NPs has the shape of a sphere and with ranges in sizes from of 85, 47, and 32 nanometers and a surface area of 2.1913, 1.6562, and 1.2387 m2/g for Fe.NPs, Cu.NPs and Ag.NPs, respectively. The effects of various parameters such as pH, initial CIP concentration, temperature, NPs dosage, and time on CIP removal were investigated through batch experiments. The results showed that 10 mg/L CIP was removed by 100%, 92% and 79% within 180 min using Fe.NPs, Cu.NPs, and Ag.NPs respectively. In addition to this, kinetic models of the adsorption and mechanism of CIP removal were studied. The cinematic analysis demonstrated that adsorption is a physics adsorption mechanism with an energy of 0.846 kJ.mol-1, 1.720 kJ.mol-1, and 3.872 kJ.mol-1, while the low activation energies of 17.660 kJ.mol-1, 13.221 kJ.mol-1, and 14.060 kJ.mol-1 for Fe.NPs, Cu.NPs, and Ag.NPs respectively. The kinetic removal process follows a pseudo-first-order model following a physical diffusion-controlled reaction. The data on adsorption was analyzed using the Langmuir, Freundlich, Temkin, and Dubinin models, as well as thermodynamic factors, indicating that the process is appropriate and endothermic sorption. The most practical adsorbent was Fe.NPs